Hydrogel Composite Based On Arrowroot Starch-G-Poly (Acrylamide-Co-Acrylic Acid)/Zeolite as Matrix of Controlled Release Urea Fertilizer - Sjaifullah, Achmad; Winata, I Nyoman Adi; Suhardiman, Ahmad (Indonesian Chimica Letters, 2022)
Agricultural yields can be increased through fertilization. Conventional fertilization by spreading fertilizer on agricultural land is very ineffective. As much as 40-70% of the nitrogen from urea given through conventional fertilization will be leaching. This problem can be overcome by implementing a new fertilization system, namely by applying controlled fertilizer release technology or Control Release Fertilizer (CRF). The CRF system is made by loading or mixing urea fertilizer at the time of synthesis of a composite based on Arrowroot Starch-g-poly (acrylamide-co-acrylic acid)/zeolite. Fertilizer will come off gradually during fertilizing the land. Synthesis of starch-based hydrogel composite Arrowroot Starch-g-poly (acrylamide-co-acrylic acid)/zeolite loaded or mixed with urea fertilizer, has been successfully carried out. The composite's structure characterized by IR spectroscopy and its ability as CRF has also been tested through swelling and urea release tests in distilled water, phosphate buffer pH 5, pH 7 and pH 9. The results show that the swelling capacity and urea release in distilled water > Buffer pH 7 > pH 9 > pH 5. The welling degree in distilled water, Buffer pH 5, pH 7 and pH 9 is 39.078; 18,719; 36,296 and 33,510 g.g-1 respectively and the release of urea is 2,129; 1,829; 2,110; and 2,091 mg.mL-1 respectively and they showed significant differences.